(3JYde h GMJQa (Bmicrosoft world 2003s - (3eMeO GdefUhQ(B.s ((3MdH (B:s (3OGQ GdHQGb(B,s, 2004)
(3EfTGA h JMQjQh JfSjb h MaX h aJM h YQV h GOGQI GdeSJfOGJ (B.s
(3JMQjQ hcJGHI fU(B.s
Keywords: (3GdfU (B- (3MGSH Bdi(B.s